Comparing sample survey measures of English earnings of graduates with administrative data during the Great Recession - Jack Britton; Neil Shephard; Anna Vignoles (Institute for Fiscal Studies (IFS), 2015)
This paper compares survey based labour earnings data for English graduates, taken from the UK's Labour Force Survey (LFS), with the UK Government administrative sources of official individual level earnings data. This type of administrative data has few sample selection issues, is substantially longitudinal and its large samples mean the earnings of subpopulations can be potentially studied (e.g. those who study a specific subject at a specific university and graduate in a speci?c year). We find that very broadly the LFS and administrative data show a similar distribution of graduates' earnings. However, the administrative data has considerably less gender disparity, higher high quantiles and more time series persistence. We also report on how the distribution of graduate and non-graduate earnings fell during each year of the Great Recession.
Keywords: 330; Administrative data; Graduate earnings; Human capital; Labour earnings; Labourforce survey; Quantile regression; Student loans